The Trend of public relations 2.0 in managing the reputation of institutions Practical case University of Bejaia - Mekideche , Imene Hadjer; Araibia , Mohammed Karim (International Journal of Social Communication, 2025)
This article aims to shed light on the most important and modern public Relations 2.0 tools used by university of Abderrahmane mira in general and the Vice-Rectorate of External Relations services in particular to manage its Reputation. Through communication, as a strategic element to build a positive image of the Institution under study. In addition, we used a qualitative approach, relying on observation and scientific interviews with sample members. The study reached the following results: Public relations represent the key of success in managing a reputation of university, to deal with all Stakeholders who interact with university, using modern interactive tools such as official website of university, and the official page on social media.